Agricultural production diversity, child dietary diversity and nutritional status in poor, rural Gansu Province of China - Liu, Xinghua; Liu, Chengfang; Chen, Kevin Z. (2023)
Research has shown mixed findings on the link between production diversity and household dietary diversity. The question is whether this link holds for children. In this study we exam ine the relationship between household’s agricultural production diversity and child dietary diversity, and between production diversity and child nutritional status. Smallholder farm households (n = 1067) and children (n = 1067) aged 3–16 years from two then nationally designated poverty counties in Gansu Province of China were interviewed in 2019. Produc tion diversity was assessed with the production richness score and production diversity score. Production diversity was calculated from agricultural production data covering a period of 12 months. Child dietary diversity was assessed with food variety score (FVS) and dietary diversity score (DDS). DDS was calculated based on 9 food groups using a 30-day recall method. Data were analysed using Poisson and Probit regression models. We find that both agricultural production richness score and revenue generated from selling agricul tural products are positively associated with food variety score, with the relationship being stronger for the latter. Moreover, production diversity score is positively associated with chil dren’s dietary diversity score whereas negatively associated with their probability of being stunted, but not with their probabilities of being wasted or zinc deficient. Household social economics status were also positively associated with child dietary diversity.